2014
DOI: 10.1007/s10802-014-9938-x
|View full text |Cite
|
Sign up to set email alerts
|

Paths from Mother-Child and Father-Child Relationships to Externalizing Behavior Problems in Children Differing in Electrodermal Reactivity: a Longitudinal Study from Infancy to Age 10

Abstract: Electrodermal hyporeactivity (or low skin conductance level, SCL) has been long established as a correlate of and diathesis for antisocial behavior, aggression, disregard for rules of conduct and feelings of others, and generally, externalizing behavior problems in children and adults. Much less is known, however, about how individual differences in children’s SCL and qualities of their early experiences in relationships with parents interact to produce antisocial outcomes. In a community sample of 102 familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 87 publications
6
37
0
1
Order By: Relevance
“…Sroufe, 1991; research by Allen and colleagues, Allen et al, 2003; Hare, Marston, & Allen, 2011). The observed times coded for each parent-child dyad were 81 min at each age (total 162 min for each parent-child dyad; see Kochanska, Brock, Chen, Aksan, & Anderson, 2015, for details).…”
Section: Methodsmentioning
confidence: 99%
“…Sroufe, 1991; research by Allen and colleagues, Allen et al, 2003; Hare, Marston, & Allen, 2011). The observed times coded for each parent-child dyad were 81 min at each age (total 162 min for each parent-child dyad; see Kochanska, Brock, Chen, Aksan, & Anderson, 2015, for details).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the parent’s positive affect with the child, and the child’s positive affect with the parent, we examined a dyadic construct of mutually responsive orientation (MRO) – a cooperative, trusting, supportive, and reciprocal parent–child relationship, infused with positive affectivity (Kochanska 1997). MRO has been well-established as a correlate and a cause of overall adaptive socio-emotional development, particularly a broad range of outcomes reflecting internalization of values, and regard for and compliance with rules of conduct (e.g., Kochanska 2002; Kochanska et al 2014; Kochanska and Kim 2013). The association of MRO with child internalizing disorders, however, has rarely been studied and warrants attention.…”
Section: The Present Studymentioning
confidence: 99%
“…Although a number of studies have shown that child temperamental characteristics (noted above) or physiological responses (e.g., Erath, El-Sheikh, Hinnant, & Cummings, 2011; Kochanska, Brock, Chen, Aksan, & Anderson, in press) moderate associations between forms of parental control and child adjustment, to our knowledge, no published studies have examined whether similar interactive associations are evident in the peer domain specifically. Questionnaire-based measures of child reactivity or regulation have the advantage of capturing responses across a range of times and situations, yet physiological assessments can readily capture responses in specific circumstances, such as conditions of peer-evaluative stress or challenge.…”
Section: Skin Conductance Level Reactivitymentioning
confidence: 99%